The Rise and Fall of Radical Democracy in Torres, ‘Venezuela’s First Socialist City’ - Hetland, Gabriel (Espacio Abierto, 2022)
Debate on the existence and quality of democracy in Venezuela in the Chávez and post-Chávez years remains highly polarized. Many scholars view Venezuela throughout this time as an authoritarian (or competitive authoritarian) regime, while some view it as an example of radical democracy. This article uses a case study of Torres municipality to build on a third view, which emphasizes the contradictions and messiness of Venezuelan democracy under Chávez. The article shows that Torres is an example of a radical democracy in which ordinary citizens enjoyed significant real power over political decision-making. This came about through what Poulantzas terms a combined struggle inside and outside the state, with radical left forces and social movements exploiting the contradictions of the Hugo Chávez administration’s left-populist regime to build radical democracy. Torres’ experiment came under strain from 2016 on due to the consolidation of national-level authoritarianism and prolonged economic crisis. This set the stage for the end of the experiment following the November 2021 victory of an opposition mayoral candidate, which highlights the non-monolithic character of Venezuelan authoritarianism.